Sistem Informasi Berbasis Web Studi kasus Rusunawa Universitas Sam Ratulangi - Jiely Senewe; Alicia A.E. Sinsuw; Virginia Tulenan (Universitas Sam Ratulangi, 2015)
A house is one valuable investment, basically because for the use as a residence. A house main functions as a place to stay, but a house can also be used as a business with a good prospect by means of contracted or leased. The common problem that arises within this business is the lack of information regarding the house’s data. This research discuss about the making of Sam Ratulangi University Rusunawa’s web which is one of the boarding houses in Unsrat that are still not well known by most students and still using manual systems to collect data. With the Waterfall methodology, the System Design with Web-based usethis Boarding House’s Information as a Case Study and with this information can facilitate the informations needed. Like how much Rusunawa’s empty rooms and it can assist students in how to rent a room in Rusunawa. Using PHP and MySQL Rusunawa’s information can be updated and maximized. By reducing the data processing with manual system (archives), the informationsprocess (registration granting system and registration information system) can be accessed anywhere using the Internet network. Keywords: Administration, Information Systems, MySQL, PHP, Waterfall,Web. Rumah merupakan sebuah investasi yang bernilai, pada dasarnya karena rumah sebagai tempat tinggal. Fungsi rumah sebagai tempat tinggal dapat menjadi bisnis yang memiliki prospek yang baik dengan cara dikontrakkan atau disewakan. Masalah yang muncul selanjutnya adalah kurangnya informasi mengenai data rumah kos yang up to date. Pembuatan Web Rusunawa Universitas Sam Ratulangi yang merupakan salah satu rumah kos-kosan yang masih belum juga dikenal oleh sebagian Mahasiswa dan masih menggunakan sistem manual seperti arsip. Dengan metodologi Waterfall Perancangan Sistem Informasi Rumah Kos berbasis Web dengan Studi Kasus Universitas Sam Ratulangi ini dapat mempermudah Rusunawa dalam berbagi informasi kamar kosong dan membantu Mahasiswa dalam menyewa kamar di Rusunawa. Dengan Menggunakan PHP dan MySQL Rusunawa bisa lebih update dalam informasi kamar dan lebih memaksimalkan dalam mengolah data pendaftaran (registrasi) dengan mengurangi pengolahan data dengan arsip dan proses pemberian informasi dan pendaftaran dapat di akses dimana saja dengan menggunakan jaringan internet. Kata kunci : Administrasi, MySQL, PHP,Sistem Informasi,Waterfall, Web.